(untitled) (Revista Archai, 2023)
This paper addresses the contemporary thesis of psychophysical supervenience and its application to the interpretation of Aristotle’s psychological hylomorphism. It will be shown that the supervenience thesis, in its different versions, fails to explain the essential unity of the soul and of the psychophysical compound. Arguments will be provided on the basis of Aristotle’s discussion of the harmony theory of the soul (de An. I 4) and more generally on his methodological claims on the definition of the soul and of its affections (de An. I 1).